PROBLEM OF IRON PROVISION FOR THE ARTIFICIALLY FED INFANTS - E.N. Kozhevnikova (Вопросы современной педиатрии, 2007)
The given article presents data on the findings of the two large clinical studies performed in Sweden, whose purpose was to examine the degree of the iron uptake from the breast milk substitutes of the new generation by the children (reduced protein contents, enrichment by C lactalbumin and etc.), depending on the level of the enrichment and form of iron, its impact on the absorbality of other microelements. The researchers received the data, which became the basis for the new commendations for the iron contents in the breast milk substitutes that was reduced to 2c4 mg/l in Europe for the infants.Key words: infants, asiderotic anemia, breast milk substitutes.